2020
DOI: 10.1055/s-0040-1712987
|View full text |Cite
|
Sign up to set email alerts
|

Incidência e fatores de risco das complicações da cirurgia de Latarjet

Abstract: Resumo Objetivo A cirurgia de Latarjet é bem estabelecida para o tratamento da instabilidade anterior do ombro. Apresenta complicações específicas com taxas de até 30%. Nosso objetivo é avaliar a incidência e os fatores de risco associados às complicações após a cirurgia de Latarjet. Métodos Analisamos retrospectivamente 102 pacientes submetidos ao procedimento. Dividimos as complicações em três tipos: clínicas, relacionadas ao enxerto e relacionadas aos implantes. Todos os pacientes foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 22 publications
0
12
0
8
Order By: Relevance
“…6,27 Neurological injury was reported by 61 participants (19.7%). For Cohen et al, 6 the rates of neurological injury ranged from 1% to 20%, and the musculocutaneous and axillary nerves were the most frequently injured. Watchful waiting is usually enough for complete resolution of the complication.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,27 Neurological injury was reported by 61 participants (19.7%). For Cohen et al, 6 the rates of neurological injury ranged from 1% to 20%, and the musculocutaneous and axillary nerves were the most frequently injured. Watchful waiting is usually enough for complete resolution of the complication.…”
Section: Discussionmentioning
confidence: 99%
“…Watchful waiting is usually enough for complete resolution of the complication. 5,6,28 Postoperative hematoma was mentioned by 61 participants (19.7%). For Metais et al, 19 hematoma is a rare complication, with an incidence ranging from 1% to 2%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,16,17,23 Both forms present good results in functional and postoperative pain scores. 24 In a systematic review, Horner directly compared the open Latarjet technique with the arthroscopic approach and concluded that three out of five studies did not find significant differences in relation to graft positioning 20,[25][26][27] ; and two out of three studies found no statistical difference in the angle of the screws. 25,27,28 Still, there are studies that demonstrate that graft positioning in arthroscopic surgery can be challenging, as well as the proper angle of the screws.…”
Section: Discussionmentioning
confidence: 99%